Cape Herb & Spice Company : choosing a growth strategy - Maunder, Peta Krost ([London] : SAGE, 2016)
Irene Ivy-Schuurmans and Dale Kneen started the Cape Herb and Spice Company in 1992, selling their wares from a modest barrow at the Cape Town Waterfront. They were housemates with full-time jobs, but both were passionate about cooking "wacky, creative and unusual" gourmet food with interesting herbs and spices that weren't commercially available. "It was while hunting for a specific herb for a specific dish we wanted to make that we stumbled onto this idea for a business," recalls Kneen. "We thought it was unlikely we were the only foodies out there who wanted the perfect herb or spice, or combination of them, to make the perfect dish".
Originally Published in: Krost Maunder, P. (2008). Cape Herb & Spice Company: Choosing a Growth Strategy. WBS-2008-9. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on May 5, 2016).
Keywords: elektronické knihy; electronic books; Strategic planning -- Case studies